Hubungan Tingkat Pengetahuan Terhadap Sikap Aborsi pada Remaja Putri di SMA X - Devy Ika Yuliyanti; Tutik Rahayu; Sri Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2025)
The level of knowledge about abortion attitudes among adolescents in Indonesia is still minimal about abortion knowledge the number of unwanted pregnancies in Indonesia is around 17.5% in adolescents aged 14-19 years, and 20% of abortions are carried out by adolescents. The purpose of this study was to determine the relationship between the level of knowledge and abortion attitudes in female adolescents at SMA X. this study is a type of quantitative research with a cross sectional approach. Data collection was carried out using a questionnaire. The number of respondents was 91 people with a proportional sampling technique, one of which is simple random sampling. The data obtained were processed statistically using the chi-square formula. Based on the results of the analysis, 91 research respondents were obtained, most of whom had age characteristics of adolescents aged 10-18 years, the gender in this studi was female, the results of the study also showed that 91.2% had high knowledge, 8.8% had sufficients knowledge, 2.2% had negative abortion attitudes, 97.8% had positif abortion attitudes. The consclusion of of this study is that there is a relationship between the level of knowledge and attitudes towards abortion in female adolescents at SMA X. With p-value of 0.03˂0.05.